Characterization of persistent symptoms after SARS-CoV-2 infection: Post COVID 19 persistent symptoms (Actualizaciones en Sida e Infectología, 2021)
Background: It is frequent that patients complain of persistent symptoms after an episode of COVID-19 infection, that worsened their quality of lifeAim: the aim of this study is to describe the main symptoms during a COVID-19 infection and persistent symptoms a month and three months after the episode. Our secondary objective is to describe the period between the COVID-19 episode and resuming work/ studies and exercise routine.  Methods: this is a descriptive, observational study that included adults who underwent an episode of SARS-CoV-2 infection. Participants responded to an online survey. We include demographic and comorbidity data and symptoms during infection, and  one and three months after infection. Results: 308 people responded to the survey, frequent symptoms during the episode included myalgia and fever. A month after the episode, 96% complained of persistent symptoms, most frequently myalgia and fatigue. Three months after the episode 38.85% complained of  persistent symptoms , most frequently  fatigue and anosmia. Only 45.7% could resume work/ studies 10 days after the diagnosis, and 17% could resume exercise routine 10 days after the diagnosis. Conclusions: there is a high percentage of people who persisted with symptoms after a COVID-19 infection. We noticed symptoms improved over time, this finding  could be encouraged for patients who persist symptomatic after the episode.
Keywords: post covid, SARS-CoV-2, COVID-19, persistent symptoms